Identification of the Starting Points of the Environmental Responsibility of a Transport Company Based on Multi-criteria Analysis - Gogolova, Martina; Vartiak, Lukas; Kovalova, Erika (International Journal of Energy Economics and Policy, 2023)
Nowadays, the problem of environmental pollution and damage extends beyond the borders of individual countries. Thanks to progress in the scientific and technical field, the impact of human activity on the environment has been significant, which has caused damage and reduced the overall value of the surrounding environment. The paper aims to point out the environmental responsibility of companies in the field of public passenger transport as one of the possible forms of obtaining a better competitive position. An essential step in processing this issue was obtaining theoretical knowledge regarding the environmental responsibility of companies. We gained theoretical knowledge by studying domestic and foreign literature, emphasising scientific works devoted to the solved problem and published in impact journals. We applied the theoretical knowledge to a specific company in Slovakia’s public passenger transport field, making it easier to understand the problem. As a result, more ecological and economic measures in the business to prevent environmental damage and reduce costs are to be introduced. To conclude, the analysed company could use saved funds for marketing activities to acquire new and retain current customers or improve its current competitive position.